2017
DOI: 10.3389/fnana.2017.00069
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of White Matter Neurons at the Gyral Crowns and Sulcal Depths in the Rhesus Monkey

Abstract: Gyrencephalic brains exhibit deformations of the six neocortical laminae at gyral crowns and sulcal depths, where the deeper layers are, respectively, expanded and compressed. The present study addresses: (1) the degree to which the underlying white matter neurons (WMNs) observe the same changes at gyral crowns and sulcal depths; and (2) whether these changes are consistent or variable across different cortical regions. WMNs were visualized by immunohistochemistry using the pan-neuronal label NeuN, and their d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 57 publications
10
13
0
Order By: Relevance
“…While the current study is based on a single specimen, this individual showed no neuropathologies and was in excellent condition when euthanized. Moreover, our results regarding the distribution, neurochemistry, and density gradients of WMICs in the lar gibbon are generally consistent with those previously reported in other mammalian species, including other primates (Barbaresi, Fabri, & Mensa, ; Barone & Kennedy, ; Chun & Shatz, ; Clancy et al, , ; García‐Marin et al, ; Meyer et al, ; Mortazavi et al, , ; Reep, ; Tomioka & Rockland, ). Thus, we assume that the description provided herein is likely to be representative of the lar gibbon as a species, but temper the strength of our conclusions according to the limitation of only having examined a single specimen.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…While the current study is based on a single specimen, this individual showed no neuropathologies and was in excellent condition when euthanized. Moreover, our results regarding the distribution, neurochemistry, and density gradients of WMICs in the lar gibbon are generally consistent with those previously reported in other mammalian species, including other primates (Barbaresi, Fabri, & Mensa, ; Barone & Kennedy, ; Chun & Shatz, ; Clancy et al, , ; García‐Marin et al, ; Meyer et al, ; Mortazavi et al, , ; Reep, ; Tomioka & Rockland, ). Thus, we assume that the description provided herein is likely to be representative of the lar gibbon as a species, but temper the strength of our conclusions according to the limitation of only having examined a single specimen.…”
Section: Discussionsupporting
confidence: 91%
“…Our analysis showed significant decreases in WMIC densities with depth in the white matter, that the densities are higher deep to gyral crowns rather than sulcal fundi, and that of all the subcortical white matters regions examined, that deep to the primary visual cortex exhibited the highest densities. While these findings are, for the most part, in agreement with previous qualitative assessments of the variation in WMIC densities (Barbaresi et al, 2014;Barone & Kennedy, 2000;Chun & Shatz, 1989;Clancy et al, 2001Clancy et al, , 2009García-Marin et al, 2010;Meyer et al, 1992;Mortazavi et al, 2016Mortazavi et al, , 2017Reep, 2000;Tomioka & Rockland, 2007), the increased density beneath primary visual cortex is of particular interest. It is well known that the primary visual cortex in primates exhibits a cell density at least two times higher than other cortical (reflecting the lower cortical cell densities in motor cortical regions, e.g., Collins et al, 2016;Turner et al, 2016) are only 1.5 times the median densities observed in the parietal and temporal lobes.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results showed widespread labeling of both superficial and deep WMNs, demonstrating that this circuit is phylogenetically conserved across species and extending our knowledge concerning the local and long‐distance projections of these neurons. In fact, although several publications have characterized WMNs in terms of density, morphology, and neurochemical heterogeneity (rat: Clancy, Silva‐Filho, & Friedlander, ; human: Meyer, Wahle, Castaneyra‐Perdomo, & Ferres‐Torres, ; García‐Marín, Blazquez‐Llorca, Rodriguez, Gonzalez‐Soriano, & DeFelipe, ; NHP: Mortazavi, Wang, Rosene, & Rockland, ; Mortazavi, Romano, Rosene, & Rockland, ; Swiegers et al, and references therein), only scant attention has been paid to their connectivity.…”
Section: Introductionmentioning
confidence: 99%